Anthurium perezfarrerae (Araceae: sect. Andiphilum), a new species from Sierra de Juárez, Oaxaca, Mexico - Pedro Díaz-Jiménez; Thomas B. Croat; Marco Cedeño-Fonseca; Héctor Gómez-Domínguez; Orlando O. Ortiz; Pedro A. Aguilar-Rodríguez (Revista Mexicana de Biodiversidad)
Mexico possesses at least 59 taxa of Anthurium, 49 species and 10 infraspecific taxa, 32 of which are found in the State of Oaxaca, Mexico. During fieldwork conducted in 2019 in Sierra de Juarez, northern Oaxaca, we discovered a previously undescribed species of Anthurium sect. Andiphilum (Schott) Croat. The new species, Anthurium perezfarrerae Díaz Jim. & Croat, is described taxonomically and illustrated. It is morphologically similar to Anthurium andicola Liebm. that is distributed in the same area, but this species differs in having a shorter geniculum, fewer primary lateral veins per side, tertiary vein prominolous above, and a shorter spadix.